Desempenho muscular e equilíbrio postural em idosas frágeis residentes na comunidade - Freire, Aline do Nascimento Falcão (2009)
Human aging is physiological process causes alterations in several systems of the organism. In the musculoskeletal system, a main change is the decreased muscle strength, that in the lower extremity, compromises the ability to respond quickly with enough strength to prevent falls, causing alterations in postural balance. Currently, many researchers have study the human frailty, defined as a multifactorial syndrome, with excess of vulnerability to stressors, reducing ability in maintaining or regulating homeostasis. Its characteristics are directly related to physical function. Aim: To analyze muscle performance and postural balance in frail and pre-frail elderly women, and to compare them according with the frailty phenotypes criteria proposed by Fried 2001. Method: 39 frail elderly women living in the community, aged 65 years and older, were assessed muscle performance of lower extremity using isokinetic dynamometer and postural balance using Berg s balance scale and computerized baropodometry. Results: There was significant difference in plantar flexor, knee flexor and knee extensor strength, in anteroposterior (AP) oscillation with eyes open and on Berg s scores between groups. A weak correlation was observed between strength and balance. Conclusion: The results suggest that the frail elderly present worse muscle performance in lower extremity and worse postural balance compared to the pre-frail elderly. There were correlations between muscle performance and balance impairments in these elderly, but several variables are also involved in maintaining postural balance